Employment Contracts for the New World of Work. - Nel (Snr), Jan Kemp. (Knowledge Resources, 2021)
Employment Contracts for The New World of Work deals with the employment contract in South Africa and the importance of this document as the foundation of the commercial relationship between the employee and the employer. _x000D__x000D_It provides practical assistance and information to the entrepreneur, business owner, front-line manager, trade union representative and official, who is, no matter how experienced, always in need of a quick reference guide and source of knowledge._x000D__x000D_Content includes:_x000D__x000D_* Identifying the Parties to The Contract_x000D_* The Legislative Framework_x000D_* The Contract of Employment: Formation, Contents and Format_x000D_* Termination of Employment_x000D_* Pushing the Frontiers of Traditional Employment - Working from Home (WFH) And Hybrid Working_x000D_* Repudiation Breaches of Contract and Remedial Rights_x000D_* Disputes and Dispute Processes_x000D__x000D_Includes a FREE TOOLKIT with sample contracts, guidelines, policies, procedures and statutory regulations.